Choice white grease used for manufacturing a protein-encapsulated fat blend source for neonatal calves - David P. Casper; Mark F. Scott (Journal of Dairy Science)
ABSTRACT: Protein-encapsulated fat (PEF) blends are routinely used for manufacturing calf milk replacers (MR). The use of PEF blends improves fat mixability to ensure MR when mixed and fed as a homogeneous solution for neonatal calves. A new alternative PEF based on choice white grease (CWG) has been developed to improve its mixability and solubility to ensure a homogeneous MR solution. The alternative PEF is hypothesized to support similar growth performance (ADG, DMI, and feed efficiency) of neonatal calves and potentially reduce costs. The study objective was to evaluate CWG PEF as an alternative to a standard animal lard–tallow (ALT) PEF blend to mix a MR to be fed to Holstein calves. A total of 40 Holstein bull calves (2–5 d old) were blocked by BW and randomly assigned to 1 of 2 treatments (n = 20/treatment) using a randomized complete block design. The treatments were (1) CWG used to manufacture a PEF blend, and (2) ALT used to manufacture a PEF blend. The PEF blends were then used to manufacture 2 experimental MR. Both MR were formulated to contain a ratio of 22% CP to 20% fat with Met, Lys, Thr, Trp, and Val AA specifications, and fed twice per day along with ad libitum 22% CP mini-pelleted calf starter (CS) and water. The MR were fed at 15% solids at 0630 and 1800 h, fed at 0.567 kg/d for d 1 to 14, increased to 0.85 kg/d for d 15 to 35, and reduced to once per day at 0.425 kg/d for d 36 to 42 to facilitate weaning at 42 d with ad libitum CS fed for the remainder of the 56-d study. Calves fed CWG and ALT PEF blends were similar (P > 0.10) in BW gain (37.4 and 35.9 kg for CWG and ALT, respectively), ADG (679.8 and 652.7 g/d), CS DMI intake (0.69 and 0.67 kg/d), total DMI (1.19 and 1.17 kg/d) and feed conversion (0.559 and 0.543 kg/kg). No significant differences were detected in frame gains and fecal scores among treatments. Choice white grease can be used to manufacture a PEF blend for use in manufacturing MR for feeding neonatal calves by maintaining growth performance and health at potentially lower cost.